(untitled) (Journal of Economic Research & Business Administration, 2019)
The article discusses the emergence of an entrepreneurial network. Such a network allows you to expand the resource capabilities of its member enterprises while maintaining their flexibility. This aspect of the study phase of the emergence of network structures and the problems of their management is not well understood and described in the literature. The particular thinking of successful managers helps to effectively solve problems, to quickly scale up the business and achieve strategic goals. The proposed business model of nanocorporations based on outsourcing and franchising rely precisely on management thinking and innovation. The model of nanocorporation involves a set of independent, specialized supplier companies with a coordinating integrator. In nanocorporations business processes are directed not only inside the organization, but rather towards integration with suppliers and building long-term relationships (networking). An integrator company develops core competencies and specializes in corporate governance, planning, marketing, and outsourcing many functions. An expanding affiliate business network ensures fast business growth, cost minimization, and high mobility. The article examines the process of creating a franchise network, which ensures its rapid growth, on the example of Kazakhstan’s trading companies. On the basis of the analysis performed, the stages of decision-making sequence are proposed for creating business networks. In this article the case study method is used as the main one.